UCP2 as a Potential Biomarker for Adjunctive Metabolic Therapies in Tumor Management - Vallejo, Frederic A.; Vanni, Steven; Graham, Regina M. (Frontiers in Oncology, 2021)
Glioblastoma (GBM) remains one of the most lethal primary brain tumors in both adult and pediatric patients. Targeting tumor metabolism has emerged as a promising-targeted therapeutic strategy for GBM and characteristically resistant GBM stem-like cells (GSCs). Neoplastic cells, especially those with high proliferative potential such as GSCs, have been shown to upregulate UCP2 as a cytoprotective mechanism in response to chronic increased reactive oxygen species (ROS) exposure. This upregulation plays a central role in the induction of the highly glycolytic phenotype associated with many tumors. In addition to shifting metabolism away from oxidative phosphorylation, UCP2 has also been implicated in increased mitochondrial Ca2+ sequestration, apoptotic evasion, dampened immune response, and chemotherapeutic resistance. A query of the CGGA RNA-seq and the TCGA GBMLGG database demonstrated that UCP2 expression increases with increased WHO tumor-grade and is associated with much poorer prognosis across a cohort of brain tumors. UCP2 expression could potentially serve as a biomarker to stratify patients for adjunctive anti-tumor metabolic therapies, such as glycolytic inhibition alongside current standard of care, particularly in adult and pediatric gliomas. Additionally, because UCP2 correlates with tumor grade, monitoring serum protein levels in the future may allow clinicians a relatively minimally invasive marker to correlate with disease progression. Further investigation of UCP2’s role in metabolic reprogramming is warranted to fully appreciate its clinical translatability and utility.